Measuring ICT readiness of instructors at the royal Malaysian Navy Training Centers - Ismail, Mohd Arif; Mahmud, Rosnaini; Awang, Janudin (Eurojournals, 2009)
In the context of Malaysia, ICT training for the personnel of the Royal Malaysian Navy is vital in keeping pace with the new technology. This paper reports the findings based on a pilot study involving thirty instructors randomly selected as respondents from one of the Army Apprentice Trade Schools in Malaysia. The main purpose of this paper is to describe the process in determining the suitability of all the items in the ICT readiness instrument which would be used in the actual study. Three aspects of the ICT readiness (basic ICT knowledge and skills, and attitudes) were tested for their validity and reliability. The ICT knowledge test comprised of 30 multiple-choice questions with four alternatives, the ICT skills test was a practical competency test based on six different applications using Microsoft Word, PowerPoint, Excel and Access, basic Internet and e-mail. The attitudes toward ICT questionnaire consisted of 44 items related to four domains: usefulness, confidence, anxiety and aversion. All the three subscales in the instrument were adapted from Rosnaini (2006), Banister & Vannatta (2006) and Wong (2002). Results from the pilot study have shown that the items to measure ICT readiness have good discriminating quality, validity and reliability.